Molecular signatures of Haemonchus contortus infection in sheep: A comparative serum proteomic study on susceptible and resistant sheep breeds - Chagas, Ana Carolina S.; Ribeiro, David M.; Osório, Hugo; Abreu, Ana A.P.; Okino, Cintia H.; Niciura, Simone C.M.; Amarante, Alessandro F.T. [UNESP]; Bello, Hornblenda J.S.; Melito, Gláucia R.; Esteves, Sérgio N.; Almeida, André M. (Elsevier, 2024)
Due to the negative impact of Haemonchus contortus in the tropics and subtropics, the detection of serum protein profiles that occur in infected sheep is of high relevance for targeted selective treatment strategies (TST). Herein, we integrated proteomics with phenotypic traits to elucidate physiological mechanisms associated to H. contortus infection in susceptible (Dorper – D) and resistant (Santa Inês – S) sheep breeds. Naïve female lambs were infected with H. contortus third-stage larvae on day zero (D0), and samples were collected weekly, for 28 days. Feces were used for individual fecal egg counts (FEC) blood for packed cell volume (PCV) and serum for specific antibody quantification through ELISA. Sera was collected on D0 (-) and D21 (+), and analyzed using a LC-MS/MS based proteomics approach. FEC, PCV, and anti-H. contortus antibody levels confirmed the absence of infection on D0. On D28 there was a significant difference between the two breeds for logFEC means (D = 3774 and S = 3141, p=0.033) and PCV means (D = 16.3 % and S = 24.3 %, p=0.038). From a total of 754 proteins identified, 68 differentially abundant proteins (DAPs) were noted. Phosphopyruvate hydratase (ENO3) was a DAP in all comparisons, while S+ vs D+ and S- vs D- shared the highest number of DAPs (8). Each of the four experimental groups clustered separately in a principal component analysis (PCA) of protein profile. Among the DAPs, proteins associated with the innate and adaptive immune system were detected when comparing S- vs D- and S+ vs D+. In D-, some proteins were linked to stress response to handling, sampling and heat. Focusing on the consequences of infection in each breed, in the D+ vs D- comparison, upregulated proteins were associated with inflammation control and immune response, where downregulated proteins pointed to a negative impact of infection on tissue anabolism, compromising muscle growth and fat deposition. In the S+ vs S- comparison, upregulated proteins were related to immune response, while the downregulated proteins were possibly linked to muscular development and growth, impaired by infection. Collectively, it can be concluded that ENO3 regulation emerges as a potential factor underlying the differential immune response observed between Santa Inês and Dorper sheep infected with H. contortus. In turn, detected acute phase proteins (APPs) reinforce their relation with infection, inflammation and stress conditions, whereas THEMIS-like may contribute to the immune system in Dorper. GSDMD, Guanylate-binding protein and ACAN warrant further investigation as possible biomarkers for TST strategy development.
Keywords: Dorper; Haemonchus contortus; Host resistance; Proteomics; Santa Inês; Sheep